The Effectiveness of Positive-Focused Mindfulness Therapy on Mental Well-being, Quality of Life, and Stress Coping Strategies in Women with Bipolar Disorder - Karbasi, Fatemeh; Shahnifeiz, Kosar; Rezaie, Vafa Ali; Ostovarzadeh, Maryam (Psychology of Woman Journal, 2023)
Objective: The primary aim of the present study was to determine the effectiveness of positive-focused mindfulness therapy on mental well-being, quality of life, and stress coping strategies in women with bipolar disorder in Tehran.Methods and Materials: This research was conducted as a quasi-experimental study with pre-test, post-test, and a control group. The study population included all women with bipolar disorder who visited Razi Hospital. Initially, individuals who had a record at these centers or were referred by specialists were contacted for registration, and 30 participants who met the study criteria were selected. The sample was randomly divided into two groups: experimental and control, and the study was conducted on them. The positive-focused mindfulness therapy consisted of 12 sessions of 90 minutes each, based on the mindfulness training protocol. Meanwhile, the control group received no training. The instruments used in this study included the 26-item Quality of Life Questionnaire (1996), the 45-item Mental Well-being Questionnaire by Keyes and Magyar-Moe (2003), and the 18-item Life Stress Questionnaire (1993). Analysis of Variance (ANOVA) was used to test the hypotheses.Findings: The results showed significant differences in the scores of quality of life, mental well-being, and stress between pre-tests and post-tests of the experimental group compared to the control group (P